Transurethral Incision of the Bladder Neck at Three Points with a Needle-Type Electrode for Bladder Neck Contracture - Cao, Guihua; Liu, Liangcheng; Du, Jianping; Li, Wei; Li, Qiang; Luo, Na; Liu, Xun; Zhou, Junjie; Wu, Tao (Frontiers in Surgery, 2022)
Purpose: This study aims to evaluate the efficacy of transurethral incision of bladder neck (TUIBN) at three-points with needle electrode for treatment of bladder neck contracture (BNC). Materials and Methods: Between January 2016 and April 2021, the bladder necks from 53 patients with BNC after surgery were incised by the needle electrode at the 5, 7, 12 o'clock positions. Patient's preoperational characteristics, peri-and postsurgical outcomes, such as time of operative, postoperative bladder irrigation, and postoperative hospital stay, as well as data of the international prostate symptom score (IPSS), maximum flow rate (Qmax) and postvoid residual (PVR), were recorded 1 and 6 months after surgery. Results: All 53 cases of BNC were successfully treated in (37.3±14.6) mins with (19.2±8.4) hrs for postoperative bladder irrigation with little intra-operative bleeding ( less than 50 mL.).The postoperative hospital stay ranged from 2 to 8 days, mean (4.0±1.6) days. No major intraoperative or postoperative complications were observed. All cases underwent follow-up assessment at 3 and 6 months after the surgery showed significantly decreased IPSS, PVR and increased Qmax compared to pre-operation (P<0.001) . Of these 53 patients , there were no recurrence in severe BNC patients, but a total 5 of 53 (9.4%) BNC patients developed BNC again within 6 months and required repeat TUIBN. Thirty patients comprised 5 recurrent cases with a follow-up period of more than 1 years. Conclusions: TUIBN at three-points provides a safe, effective and reliable option in treating patients with BNC.